2022
DOI: 10.1149/2162-8777/ac7821
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of p-Type Copper Gallium Oxide (CuGaO2) Thin Films by Dual Sputtering Using Cu and Ga2O3 Targets

Abstract: For the first time, this research focuses on the deposition and characterization of radio frequency (RF) sputtered p-type CuGaO2 thin films using the dual-target sputtering technique with Cu and Ga2O3 targets. The sputtering power to the Cu target was varied from 5W to 50W while having the Ga2O3 sputtering power constant at 200W. The deposited films were subsequently annealed at two different annealing temperatures of 800℃ and 900℃ in N2 ambiance. The effects of variation in Cu sputtering power and annealing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(60 reference statements)
2
6
0
Order By: Relevance
“…It is important to note that there is an absence of satellite peaks corresponding to the Cu-doublet that appears towards the higher energy side of the main peaks. A similar absence of satellite peaks has been reported previously in the literature that report single-phase Cu-based delafossites [35,36,57].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is important to note that there is an absence of satellite peaks corresponding to the Cu-doublet that appears towards the higher energy side of the main peaks. A similar absence of satellite peaks has been reported previously in the literature that report single-phase Cu-based delafossites [35,36,57].…”
Section: Resultssupporting
confidence: 89%
“…The delafossites obtained using the addition of Cu+ cation are called Cu-based delafossites, which have a chemical formula of CuMO 2 , where Cu is the positive monovalent cation (Cu + ), M = Al 3+ , Cr 3+ , In 3+ , Ga 3+ , Sc 3+ , and Y 3+ (trivalent cation), and oxygen is the divalent anion (O 2− ) [34]. This understanding provided a new dimension that led to a recent spike in the interest in p-type TCOs, particularly Cu-based delafossites [35][36][37]. It has been identified that Cu-based delafossites typically possess a high optical transparency (60%-85%) and a low electrical resistivity (5 × 10 −2 to 8 × 10 −3 Ω-cm) [31,38].…”
Section: Introductionmentioning
confidence: 99%
“…In the annealed samples at higher temperatures, the spinel phase becomes less and less and completely disappears in S900 sample. Saikumar et al 34 , also showed that the spinel phase is formed through the sputtering method at a temperature lower than 800 °C. Varadarajan et al 39 showed that the spinel phase is actually a meta-stable phase that forms at low temperatures and practically disappears at temperatures above 700 °C.…”
Section: Resultsmentioning
confidence: 98%
“…But in low temperatures, the necessary reactive energy is not high enough to form the delafossite phase 33 . It has been revealed that pure copper-based delafossite is attained at high temperatures 34 . As Yu et al 6 pointed out, the delafossite CGO is formed only at temperatures higher than 600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…35 This understanding led to a new dimension and a recent spike in research related to p-type TCOs, especially Cu-based delafossite thin films. [36][37][38] The Cu-based delafossites typically have high optical transparency (60% − 80%) and improved electrical conductivity (5 × 10 −2 to 8 ×10 −3 Ω.cm). 39,40 Ag can also be used as an appropriate cation for the CMVB technique, but the resultant film had a comparatively poor electrical conductivity (10 4 to 10 6 Ω.cm).…”
mentioning
confidence: 99%